Tear Resistance Evaluation of Room Temperature Vulcanizing Silicone Rubber: A Comparative Study - Mawandi, F.R.; Safitri, P.D.; Mirnanda, D.; Nurrokhim, F.H.R.; Adyono, Ndaru; Lestari, Wahyu Dwi (Universitas Negeri Malang, 2025)
Room Temperature Vulcanizing (RTV) silicone cures at room conditions, providing tear resistance and flexibility to a wide range of industries. Yet, its mechanical performance improvement continues to be difficult when it is filled and catalyzed. In this work, the tear resistance of three RTV materials—RTV 48, RTV 683, and RTV M4503—is investigated with different talc (2–4 wt.%) and catalyst (40–60 wt.%) formulations. Tear resistance testing per ASTM D624 yielded average and standard deviation values for material consistency determinations. Comparative analysis is also given in the research to ascertain the effect of over-cross-linking on elasticity and structural morphology. RTV 48 experienced a dramatic decrease in tear strength at high catalyst content due to over-cross-linking and the loss of elasticity. RTV 683 experienced initial improvement through the addition of talc, but excess catalyst caused premature cure and reinforcement loss. In contrast, RTV M4503 showed significant tear resistance enhancement as talc and catalyst were compounded optimally, maintaining structural integrity and reinforcement efficacy. Results demonstrate the crucial role of filler and curing agent concentration interaction in modulating silicone mechanical properties. RTV M4503 featured the optimal tear resistance and stable performance among the compositions assessed, indicating its potential use in applications requiring enhanced durability. This research provides a guide to optimization of additive ratios in RTV silicone formulations, guiding materials and process conditions selection for industrial applications that demand reproducible mechanical strength.